Effect of Potassium Fertilizer and Humic Acid Doses on Peanut (Arachis hypogaea) Yields - Chairunnisa Faza Nabillah; Sutini Sutini; Nora Augustien Kusumaningrum (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This research aims to determine the best dose of KCl fertilizer and humic acid for peanut yields. The study was conducted using a split-plot design with two factors, and each factor was repeated three times. The dose of KCl as a subplot consisted of 4 levels (0, 50, 75, and 100 kg/ha), while humic acid as the main plot consisted of 4 levels (0, 10, 20, and 30 kg/ha). Observation included the number of non-productive gynophores, the number of pods, dry weight harvest yield (pods per plant, pods per plot, seeds per plant, and seeds per plot), and the weight of 100 seeds. The single factor of KCl dosage significantly affected the dry weight of pods per plant, dry weight of seeds per plant, and dry weight of seeds per plot. The single factor of humic acid treatment had no significant effect on all observation variables, while the interaction of KCl and humic acid doses significantly affected the number of non productive gynophores and the weight of 100 seeds. The best dosage was 100 kg/ha, producing the highest yield with a dry seed weight per plot of 147.43 g. The combination of KCl 75 kg/ha and humic acid 30 kg/ha produced peanuts with the best quality, with weight 100 seeds of 39.47 g. Keywords: Humic acid, KCl, Peanut, Potassium, Yield.